Effects of Capsaicin and Carbachol on Secretion From Transplanted Submandibular Glands and Prevention of Duct Obstruction. Issue 4 (April 2016) - Su, Jia-Zeng; Liu, Xiao-Jing; Wang, Yang; Cai, Zhi-Gang; Zhang, Lei; Lv, Lan; Wang, Zhen; Hong, Xia; Yu, Guang-Yan
Abstract : Purpose: To investigate whether capsaicin and carbachol promote secretion from and prevent duct obstruction in transplanted submandibular glands (SMGs). Methods: This retrospective cohort study included consecutive patients with severe keratoconjunctivitis sicca and successful SMG transplantation. Patients were divided into 2 groups: an exposed group receiving both capsaicin and carbachol after surgery and an unexposed group receiving neither. Secretion changes in response to capsaicin and carbachol administration were recorded in the exposed group. The main outcome measures were the secretory flow rate and duct obstruction rate in the transplanted SMGs. Results: Forty-four patients (44 eyes) in the unexposed group and 115 patients (128 eyes) in the exposed group were followed up for more than 3 months postoperatively. The baseline characteristics were similar between the groups. The secretory flow rate before and 5, 25, 55 minutes after administration was 1 mm (0–2 mm) (median with interquartile range), 3 mm (1–5 mm), 4 mm (2–5 mm), 1 mm (0–2.5 mm), respectively, for capsaicin and 1 mm (0–3 mm), 1050 mm (450–1500 mm), 375 mm (150–600 mm), 0 mm (0–150 mm), respectively, for carbachol ( P < 0.001 for both). In the exposed group, 6.2% of eyes had duct obstruction, whereas 18.2% of eyes in the unexposed group had duct obstruction ( P = 0.031) (odds ratio = 0.3, 95% confidence interval, 0.105–0.856). Conclusions: This study provides evidence that capsaicin and carbachol effectively promote secretion from and prevent duct obstruction in transplanted SMGs during at least 3 months after transplantation.